Integrated primary care: patient perceptions and the role of mental health stigma. (19th June 2019) - Miller-Matero, Lisa R.; Khan, Shehryar; Thiem, Rachel; DeHondt, Tiffany; Dubaybo, Hala; Moore, Daniel
Abstract: Some patients are more willing to see a behavioral health provider within primary care. The purpose of this study was to evaluate the patients' perspectives of having access to a psychologist within primary care and to investigate whether mental health stigma affected preferences. In total, 36 patients completed questionnaires after seeing a psychologist in primary care. Patients were satisfied with having a primary care psychologist involved in their care. Most patients were more likely to see the psychologist in primary care and those who preferred this indicated higher levels of mental health stigma. The overarching theme for why patients saw a psychologist in primary care was convenience. Mental health stigma may also have played a role. Results suggest that providing integrated services may reach patients who may not have otherwise sought services in a behavioral health clinic. Findings from this study encourage the continued integration of behavioral health services.